1983
DOI: 10.1016/s0006-3495(83)84288-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cholesterol content on red cell membrane viscoelasticity and fluidity

Abstract: The purpose of this investigation was to correlate the viscoelastic properties and lipid fluidity of the red blood cell membrane to its lipid composition. The viscoelastic properties of human red cells that had been enriched or depleted in cholesterol were determined by the micropipette technique. The lipid fluidity of the outer and inner leaflets of the erythrocyte membrane was concurrently assessed by steady state fluorescence depolarization. The elastic modulus and the viscosity moduli of the erythrocyte me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
80
2
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(89 citation statements)
references
References 17 publications
6
80
2
1
Order By: Relevance
“…Both parameters are significantly increased. 111 terms of flexibility, this finding is in agreement with that of Chabanel et a1 (21) and was also found in rats experimentally exposed to lead (27). Concerning increased aggregation, no data are available.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Both parameters are significantly increased. 111 terms of flexibility, this finding is in agreement with that of Chabanel et a1 (21) and was also found in rats experimentally exposed to lead (27). Concerning increased aggregation, no data are available.…”
Section: Discussionsupporting
confidence: 91%
“…Qualitatively, these viscoelastic curves imply erythrocytes showing an enhanced rigidity (18)(19)(20). Biochemical investigations have demonstrated that erythrocyte cholesterol is increased in lead-exposed workers (I I) and that the fluidity of the cholesterol-enriched erythrocytes is decreased (21). Moreover, in vitro experi~nents have shown that the membrane viscosity of erythrocytes is increased after incubation of ghost membranes for erythrocytes with lead for 1 h (22).…”
Section: Discussionmentioning
confidence: 99%
“…Membrane lipid order is influenced by various factors, including changes in lipid composition, the concentration of membrane cholesterol, the density of lipid packing, relative water content, ion concentration, pH, and temperature, and shear stress may alter membrane lipid order via any of these factors or combinations of them. Studies on living cells and membrane models have shown that the cholesterol content of the membrane has a major impact on the physical properties of plasma membranes, including on their membrane fluidity (Chabanel et al, 1983;Coderch et al, 2000). In the present study, treatment of ECs with MbCD, which depletes membrane cholesterol, was found to decrease the membrane lipid order, and the addition of cholesterol prevented the effects of MbCD.…”
Section: Discussionsupporting
confidence: 51%
“…The effect of lipid composition modulation on red blood cells has been extensively studied. Indeed, the rheology of erythrocytes is altered in patients with hypercholesterolemia due to an in- creased cholesterol:PL ratio and impaired membrane fluidity (23,24). Statin treatment lowers the cholesterol amount in the membranes and normalizes erythrocyte membrane fluidity (10,25).…”
Section: Discussionmentioning
confidence: 99%